Farmer premiums for the voluntary adoption of conservation plans - Joseph C. Cooper; Giovanni Signorello (Fondazione Eni Enrico Mattei (FEEM), 2002)
Utilizing the random utility and random profit difference approaches, we develop a theoretical model that explains why farmers may require a premium in excess of the decrease in profits to adopt a conservation plan. Identification of this risk premium can aid the government in addressing approaches to lowering the costs of encouraging farmers to adopt the conservation programs. Previous work done in this area has not successfully identified this premium We estimate this premium using survey of farmers in conjunction with predictions of changes in production costs. To increase the efficiency of the econometric analysis of survey responses, we use the so-called "one-and-one-half-bound" (OOHB) elicitation format. Furthermore, to test the sensitivity of our estimation results to functional form and distributional specifications, we compare the results utilizing parametric, nonparametric, and semi-nonparametric econometric approaches.
Keywords: Q14; Q25; 330; Risk premium; contingent valuation; willingness to accept; one-and-one-half-bound discrete choice elicitation format; agri-environmental practices; Ökologischer Landbau; Agrarpolitik; Risikoprämie; Willingness to pay; Schätzung; Sizilien